OPTIMALISASI PENGELOLAAN AUDIOVISUALMENGGUNAKAN APLIKASI CAPCUT - Harits Alfaisa Hasibuan; Rina Febrina (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Audiovisual processing has become an important role in making social media content more interesting, there are many audiovisual processing applications that can be used, but audiovisual management has several obstacles, including requiring a long time, a place that is not flexible because it uses a computer or laptop, and applications that paid. This research aims to optimize audiovisual management using the CapCutapplication. . This research uses a qualitative method with a case study approach to optimize audiovisual management using the CapCut application by the Public Relations of the South Sumatra Ministry of Law and Human Rights Regional Office, with a focus on social media content uploaded by the South Sumatra Ministry of Law and Human Rights Regional Office's Public Relations. Data will be collected through direct interviews with the South Sumatra Ministry of Law and Human Rights Regional Office's Public Relations team to find out how to optimize audiovisual management using the CapCut application. In optimizing audiovisual management using the CapCut application, it was found that CapCut has advantages compared to using previous applications, namely the flexibility provided, the application usage time is quite short, and also the provision of the application for free, as well as various kinds of visual effects that can be used. , this of course increases effectiveness when managing audiovisuals. The findings of this researcher can contribute to audiovisual management actors to increase the effectiveness of these activities.